The Soil Moisture Content Determination using Interdigital Sensor - Markevicius, V.; Navikas, D.; Valinevicius, A.; Andriukaitis, D.; Cepenas, M. (Elektronika ir Elektrotechnika, 2012)
During geological soil examination humidity of the soil was decided to be measured using interdigital capacitance sensors. Using software „COMSOL v4.2“ the sensors were modelled and optimal sizes for use with AD 5933/34 chip were selected. Electrical impedance has proven to be the most suitable parameter for humidity measurement. Optimal probing frequency, geometry of the sensor and electrical impedance to humidity function were modelled. DOI: http://dx.doi.org/10.5755/j01.eee.18.10.3055